La cooperación eficaz en los delitos de carácter asociativo y el beneficio de la pena. - Freire Carrillo, Verónica Marisol (2018)
Organized crime and illegal bands well structures have passed barriers worldwide due to technological progress and the globalized world, its high economic financing forced the State to adopt criminal policies to counteract this form of crime, for this reason the legislator incorporated in the criminal procedural law the figure of effective cooperation, because it is very difficult to investigate crimes of great complexity. The figure of effective cooperation is found in the COIP within the special investigative techniques, and it occurs when the defendant get an agreement with the prosecutor's office to supply data and infonnation that collaborate with the good performance of the Investigation, and can reach to find the criminal leadership and to prevent future crimes of equal or greater severity. The data provided by the cooperator must be verifiable and subject to verification. The cooperator when providing the information for the agreement is subject to a benefit that is the reduction of the penalty by a minimum of 20% and in case of great social upheaval to a minimum of 10%. The law does not determine in which crimes the effective cooperation operates but due generally in the complex crimes, structured crimes, plurisubjectives and plurioffensives. These crimes can be trafficking in people, organ, arms trafficking, influence peddling, private enrichment not justified, testaferrisms, terrorism embezzlement, bribery, concussion, genocide, forced prostitution, extrajudicial execution, drug trafficking, murdered, etc. Effective cooperation has its structural basis in the agreement against organized crime and all its protocols, where its purpose is to prevent and eradicate crime that has a high degree of organized crime and that has crossed borders and can destabilize the state and the world economy.